2021
DOI: 10.3390/polym13050814
|View full text |Cite
|
Sign up to set email alerts
|

Bond Strength of Universal Adhesives to Dentin: A Systematic Review and Meta-Analysis

Abstract: Currently, the availability of a wide variety of universal adhesives makes it difficult for clinicians to choose the correct system for specific bonding situations to dentin substrate. This study aimed to determine whether there are any alternative techniques or additional strategies available to enhance the bond strength of universal adhesives to dentin through a systematic review and meta-analysis. Two reviewers executed a literature search up to September 2020 in four electronic databases: PubMed, ISI Web o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(81 citation statements)
references
References 164 publications
0
49
0
Order By: Relevance
“…The incorporation of PY into universal adhesives may influence their bonding performance to dentin and ameliorate the antibacterial effects against cariogenic species, such as S. mutans . An ideal restorative material should possess some antibacterial properties, along with good mechanical properties and bonding stability over time [ 1 , 21 , 36 ]. Unfortunately, the resin adhesive systems that are currently available on the market do not completely fulfill all these requirements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The incorporation of PY into universal adhesives may influence their bonding performance to dentin and ameliorate the antibacterial effects against cariogenic species, such as S. mutans . An ideal restorative material should possess some antibacterial properties, along with good mechanical properties and bonding stability over time [ 1 , 21 , 36 ]. Unfortunately, the resin adhesive systems that are currently available on the market do not completely fulfill all these requirements.…”
Section: Discussionmentioning
confidence: 99%
“…However, the bond strength and stability of resin adhesives bonded to dental tissues are important aspects to attain optimal dental restorations in an oral cavity [ 1 , 3 , 5 , 21 ]. Indeed, several studies [ 41 , 42 , 43 , 44 , 45 ] reported a severe degradation of the polymer–dentin interface over time due to a synergic hydrolytic degradation of the polymer matrix within the hybrid layer and to the enzymatic degradation of poorly infiltrated demineralized dentin collagen fibrils through activated host metalloproteinases (MMPs) and cysteine-cathepsins (CTs).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the hybrid layer is a mixture of dentin, hydroxyapatite, resin monomers and residual solvents; hence, its stability ultimately depends on the resistance of the individual components to the degradation [51]. In general, the more compact and homogeneous the hybrid layer, the more stable resin-dentin bond is created [34,52] (Figure 2b).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the resin-dentin interface produced by two-step etch-and-rinse adhesives, degraded with time when directly exposed to water or oral fluids [33]. When exposed to long-term water storage, an increase in the number of adhesive interface failures was demonstrated in in vitro studies [34,35].…”
Section: Introductionmentioning
confidence: 99%